2022
DOI: 10.1192/bjo.2021.1085
|View full text |Cite
|
Sign up to set email alerts
|

Narrative review of the COVID-19, healthcare and healthcarers thematic series

Abstract: Summary This review covers the thematic series of 22 papers selected from among manuscripts published by BJPsych Open concerning coronavirus disease 2019 (COVID-19) and healthcare. We report nine papers that cover concepts and epidemiology relating to the public and patients. We review 11 papers about the impact of COVID-19 on healthcare services and their staff in 15 countries. Two papers consider the psychosocial impact on staff working in mental health services in the UK. Most papers report cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…This finding indicates that the most difficulties are experienced by young people. Other studies have also reported that a young age is one of the predictors of the appearance of the clinical signs of mental health disorders [ 26 , 28 , 31 ]. The sensitivity of this group is also emphasized by the observation that there was an increased psychiatric hospitalization rate for younger individuals during the pandemic [ 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding indicates that the most difficulties are experienced by young people. Other studies have also reported that a young age is one of the predictors of the appearance of the clinical signs of mental health disorders [ 26 , 28 , 31 ]. The sensitivity of this group is also emphasized by the observation that there was an increased psychiatric hospitalization rate for younger individuals during the pandemic [ 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our published thematic series (and their editorial leads) are: Emerald Series ( ) (Graham Thornicroft) 12 – released 2019 Cognition in Mood Disorders ( ) (Allan Young, Richard Porter, Katie Douglas) 13 – released 2020 COVID-19, Healthcare and Healthcarers ( ) (Richard Williams, Kenneth Kaufman, Esther Murray) 14 – released 2022 Refugee and Asylum Mental Health ( ) (Cornelius Katona, Derrick Silove, Kenneth Kaufman, Pieter Ventevogel) 15 – released 2022. …”
Section: Thematic Series and Growthmentioning
confidence: 99%
“…COVID-19, Healthcare and Healthcarers ( ) (Richard Williams, Kenneth Kaufman, Esther Murray) 14 – released 2022…”
Section: Thematic Series and Growthmentioning
confidence: 99%
“…26 While recognising the high prevalence rates of significant mental illness it is also important not to overmedicalise distress and associated adaptive and transient emotional symptoms and to consider the trajectory of distress over time. 27 Key questions for the assessor include establishing whether there are multiple mental symptoms, whether they are persistent, the extent to which they are disabling and whether they exceed what would be regarded as culturally appropriate. The UNHCR has proposed an umbrella classification of 'emotional disorders' which covers depression, anxiety and PTSD and is characterised by the presence of overwhelming sadness/apathy, highly distressing re-experiencing symptoms and/or exaggerated or uncontrollable anxiety or fear persisting for at least 2 weeks.…”
Section: Comprehensive Health Assessment Programmes To Welcome Refugeesmentioning
confidence: 99%